EFFECT OF FISCIAL DECENTRALIZATION ON SERVICE DELIVERY IN INDUSTRIAL CITY DIVISION MBALE CITY - MUTUWA SARAH (My University, 2024)
ABSTRACT The study concentrated on effect of fiscal decentralization on service delivery in industrial city division Mbale, City. The study concentrated on three specific objectives of: To find out how assignment of expenditure responsibilities affects Service Delivery in Industrial City Division in Mbale City, to analyze the effect of local Taxes on Service Delivery in Industrial City Division in Mbale City, and lastly to evaluate the role of inter-governmental transfers on service delivery in Industrial City division in Mbale City. The study used a descriptive research methodology and used a mixed research approach. The study considered a sample size of 110 respondents. Study findings concluded that expenditure has an effect on services delivery, that there is Political influence in allocation that Local Governments need more powers on expenditure, that Local Governments are responsible for budgeting for services, that Local taxes increase demands for services, that Local governments do not generate adequate revenue, that Local revenue is highly misappropriated and diverted, that Government transfers are aimed at improving service delivery. The study recommends that: There should be more investments by Central Governments to lower local governments to ensure effective service delivery and lastly that there is need for the local Governments to improve on revenue collection and management.